Numerical research on effect of hydrogen blending fractions on idling performance of an n-butanol ignition engine with hydrogen direct injection. (15th December 2019) - Shang, Zhen; Yu, Xiumin; Shi, Weibo; Huang, Shan; Li, Guanting; Guo, Zezhou; He, Fengshuo
Highlights: An n-butanol SI engine with hydrogen direct injection is proposed. The idling performance with four hydrogen fractions are simulated and analyzed. Hydrogen addition can improve the combustion and emission at idle condition. The distribution of formaldehyde and acetaldehyde concentration is investigated. Abstract: In this paper, a numerical research on an n-butanol ignition engine with hydrogen direct injection was carried out, aiming to observe the effect of hydrogen blending fractions on idling performance. A three-dimensional dynamic mesh model coupled with a detailed chemical kinetic mechanism of n-butanol oxidation were established to investigate the engine combustion process in CFD software CONVERGE. And the numerical model was validated through experiments. The performance of pressure and temperature inside cylinder, HC and CO emissions and formaldehyde and acetaldehyde emissions with four hydrogen fractions were simulated and analyzed. The simulation results showed that in comparison with pure n-butanol, the peak cylinder pressure increased 18.62%, 22.86% and 25.41% at φ H 2  = 5%, φ H 2  = 10% and φ H 2  = 15%, respectively. Meanwhile, the process of heat release can be accelerated and concentrated by hydrogen blending. The HC and CO emissions decreased gradually with the increase of hydrogen fraction. The largest magnitude of reduced HC and CO emissions was at φ H 2  = 5% as 31.31% and 19.05%, respectively. In terms of unregulated emissions, the acetaldehyde emissions remained a higher level than formaldehyde emissions for all hydrogen fractions at idle condition, and both decreased with the increase of hydrogen fraction. The distribution of formaldehyde and acetaldehyde concentration were closely related to the temperature field inside cylinder. The improvement of acetaldehyde emissions affected by adding hydrogen was more significant than that of formaldehyde emissions. Through hydrogen direct injection, a local hydrogen-enriched area near the spark plug can be formed, which contributed to better combustion performance of n-butanol engine at idle condition.